Wasted: understanding the economic and social impact of food waste - Chrobog, Christian Karim (2014)
Over one-third of global food production goes to waste while over 850million people are fighting chronic hunger. The United States is the world’s largest food waster. One third of America’s food with an economic value of US$161 billion is wasted and less than 7% is recycled. American food waste ends up in landfills creating powerful methane gas emissions. South Korea, on the other hand, has implemented the world’s strictest food waste laws, and today diverts 93% of wasted food away from landfills turning such waste into powerful economic opportunities. This Master Thesis investigates the reasons behind global food waste by comparing South Korea and the US. It explores what these two nations are doing to address their respective food waste problems, South Korea successfully, the US not. The paper looks at the two countries’ respective policies and national characteristics, which impact decision-making and recycling processes. The effort concludes that South Korea has embarked on a necessary paradigm shift turning food waste into powerful economic drivers leading to a sharp decline in food waste. In the US, food waste continues to be a major problem without a national strategy to remedy waste. Any effort in the US, while laudable, is sporadic and local, and hence the US misses out on possibly important economic growth opportunities.